Relationships between locus of control and adherence to diabetes regimen in a sample of Iranians - Morowatisharifabad, Mohammad Ali (Medknow Publications, 2010)
BACKGROUND: Adequate self-care in diabetes improves quality of life and decreases the number of inpatient cases. The health locus of control theory is used to assess adherence to diabetes regimen in some studies in developed countries. The primary purpose of this cross-sectional study is to determine the status of diabetes locus of control in a sample of diabetic patients in Iran as a developing country. We investigated selected factors contributing to locus of control and adherence to diabetes regimen. MATERIALS AND METHODS: This cross-sectional study was carried out on 120 patients referred to Yazd Diabetes Research Center. The Iranian versions of Diabetes Locus of Control scale and Diabetes Self-care Activities scale were used for data collection. RESULTS: Men revealed more internal locus of control and women revealed more chance locus of control. The attributions of external locus of control increased by age, while the internal locus of control increased by education level and chance locus of control decreased by education level. A positive association between internal locus of control and adherence to diabetes regimen was found and there was a negative association between chance locus of control and adherence to diabetes regimen. CONCLUSION: Findings suggest that interventions aimed at improving internal locus of control may improve adherence to diabetes regimen but different diabetic patients have different attribution styles and interventional programs to enhance diabetes self-care will be more successful if patient's locus of control is addressed.